Solution-Processed Functionalized MoS2 Nanosheets Composite for Photodetection Application - Alexander V. Kukhta; Enliu Hong; Nadzeya I. Valynets; Sergei A. Maksimenko; Uladzislau Parkhomenka; Nikita Belko; Anatoly Lugovsky; Tatiana A. Pavich; Iryna N. Kukhta; Ziqing Li; Xiaosheng Fang (Photonics, 2023)
Charge-transfer organic-inorganic complexes have demonstrated great potential in optoelectronic applications. Herein, a drop-casting processed photodetector based on thick composite films made of multi-layered MoS2 nanosheets chemically bonded to linear molecules of aromatic thiols has been developed. Composites based on multilayered nanosheets allow for facile preparation of low-cost, large-area, and flexible devices. It was demonstrated that a simple functionalization of ultradispersed MoS2 nanosheets with linear aromatic thiol results in the formation of charge and energy transfer complexes. A photodetector with functionalized MoS2 nanosheet film prepared by drop coating with Au electrodes demonstrated enhanced performance compared to pure materials. Our first experiments illustrated that functionalization of MoS2 nanosheets by a paraquaterphenyl thiol derivative leads to a significant increase in the photoresponse speed (by a factor of 12) and decay speed (by a factor of 17.5), in addition to the enhancement of the photostability of the MoS2 based photodetector. The photo current value has been increased by about an order of magnitude. The proposed approach offers promising prospects for further development of photodetectors.